2003
DOI: 10.1046/j.1365-2206.2003.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Worries and problems of young carers: issues for mental health

Abstract: This paper reports on a research study which explored the worries and problems of young carers in Edinburgh. Sixty‐one young carers took part in the study, conducted between April and June 2002. Findings indicate that young carers identify significant worries and problems in relation to their well‐being, and that these come over and above any ‘normal’ adolescent difficulties. It is suggested that these findings may have important implications for young carers’ mental health, now and in the future, and contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
142
1
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(160 citation statements)
references
References 11 publications
8
142
1
9
Order By: Relevance
“…In this case, emotional support is present in the form of the daughter being available for her mother when the latter is feeling depressed or feeling like using drugs. The daughter's expression of her desire for time on her own is consistent with reported negative effects of young caring, as many young carers report a lack of time to themselves (Cree, 2003).…”
Section: Discussionsupporting
confidence: 63%
“…In this case, emotional support is present in the form of the daughter being available for her mother when the latter is feeling depressed or feeling like using drugs. The daughter's expression of her desire for time on her own is consistent with reported negative effects of young caring, as many young carers report a lack of time to themselves (Cree, 2003).…”
Section: Discussionsupporting
confidence: 63%
“…33,34 Our study confirmed that most were employed, half of them were receiving high incomes and less than 10% earned under $20,000 per annum. This profile suggests there may be two distinctive groups of young caregivers in the community: those providing long-term care to parents with chronic illness and those we have identified, who may be assisting the family in caring, for a shorter time, for an older or elderly relative with a terminal illness.…”
supporting
confidence: 69%
“…Cree (2003) included those aged 5-25 years, whereas the UK Department of Health (DoH, 1999) considered only those aged under 18 as young carers. Young adult carers may be differentiated from young carers in general, a broader category which includes children and adolescents.…”
Section: The Definition Of 'Young Carer'mentioning
confidence: 99%